Textile Wastewater Treatment for Basic Fuchsin Dye Removal Using Highly Efficient Nano Earthenware Clay in Fixed-Bed Reactors - Kumar, C (Springer Nature, 2025)
This research investigates the biophysical and chemical operations of toxic fuchsin dye elimination from industrial and pharmaceutical effluents using advanced nano-ceramic clays as eco-friendly wastewater treatment methods. Nano silica, nano kaolinite and nano montmorillonite were tested as efficient adsorbents through UV/Visible spectroscopy, field emission scanning electron microscope (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and Brunauer–Emmett–Teller (BET) surface area analysis. These nano-clays present excellent surface area capabilities, together with high reactivity, which makes them excellent choices for environmental cleanup operations. The optimized conditions for continuous flow column dye (fuchsin) removal experiments included a pH value of 5.5 using 7 nm particles (specific surface area of 89.37 m2/g and total pore volume of 0.986 cc/g) at a temperature of 27 °C with a bed height of 10 cm and a dye concentration of 10 mg/L and a flow rate of 5 mL/min and contact time of 9 h. The dye removal efficiency reached 99.8% when nano silica was used under these specific operating conditions. Adsorption data demonstrated excellent fittings to Clark s model (R2 = 0.9956) as well as to the Sips isotherm (R2 = 0.9966), resulting in an obtained maximum adsorption capacity (qm) of 3.62739 ± 0.7369 mg/g. The BET analysis revealed a type-IV isotherm pattern, which demonstrates a mesoporous nature in the material. The material displayed outstanding durability during initial regeneration tests since it maintained 99.7% efficiency in the first cycle. This research demonstrates that nano-ceramic clays represent an affordable, high-performing wastewater treatment technology that provides an environment friendly substitute to traditional methods and enables the development of scalable environmental solutions. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.